Addressing the Triple Trauma of Factors Leading to Perinatal Health and Mental Health Consequences in Two Upstate New York Communities - Robert H. Keefe; Robert A. Rubinstein; Kiara Van Brackle; Sanid Music; Zikora Nnam; Sandra D. Lane (Behavioral Sciences)
This article focuses on the impact of trauma experienced by individuals, families and groups, and neighborhoods in Rochester and Syracuse, New York. Using the levels of analysis put forward in Bronfenbrenner’s ecological systems theory (i.e., individual, family, and community), we argue that trauma operates at each of those levels. This mixed-methods study reviews the findings of seven previously published studies (with data collection ranging from 2000 to 2019), each of which addresses trauma among low-income residents. Specific methods include secondary analyses of births, qualitative interviews of persons who delivered a baby within the past two years, a community survey of residents living in high-crime areas, and secondary birth data to document the impact of socio-ecological risk factors on the trauma of birthing persons, their children, and their partners. Individuals and families living in high-risk neighborhoods (e.g., where residents experience frequent gun shots, racially disproportionate incarceration, and poverty) had more negative health outcomes including posttraumatic stress disorder, intrauterine growth restriction, and depression. Interventions focused on community-based practices that address individual, family, and community-level trauma must also address the multiple risk factors for trauma located in the environmental and social stressors.